Content and Principles of Financial Policy - Bakhritdinovich, Ismoilov Ravshanjon; Xodievich, Maksudov Abdumalik (European Journal of Life Safety and Stability (2660-9630), 2021)
This article discusses the views and comments on the content and principles of fiscal policy.